Liquid-liquid extraction as a sample preparation procedure for the determination of Na, K, Ca, and Mg in biodiesel - Barros, Ariane Isis; De Oliveira, Adriana Paiva; Gomes Neto, José Anchieta [UNESP]; Villa, Ricardo Dalla (Royal Society of Chemistry (RSC), 2017)
Liquid-liquid extraction is proposed as a clean sample preparation procedure for the determination of Na, K, Ca, and Mg in biodiesel by line source flame atomic absorption spectrometry (LS FAAS) and of Na and K by flame photometry (FP). A full 23 factorial design was used to optimize the sample preparation. The investigated variables were the temperature effect, the use of acid and the stirring time for the extraction of metals in biodiesel. The sample preparation method essentially consisted of extracting metals from biodiesel with an aqueous solution of HNO3 (1%, v/v) at 25 °C and manual agitation for 4 min. The instrumental limits of detection (LODs) for LS FAAS and FP were in the ranges 0.04-0.21 and 0.18-0.36 mg kg-1, respectively. The accuracy of the method was checked by means of addition and recovery tests, and the recovery results for LS FAAS and FP varied from 80 to 114%, with RSD less than 14%. No significant differences were observed (p = 0.05) between the results obtained by the proposed technique and a comparative method. Interlaboratory studies were performed using different instruments, different samples and the same analyst. For this, addition and recovery tests and CRM analyses were performed by high resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS) and FP. The recoveries varied from 84 to 107%, with RSD less than 11% and the results for Na, K, Ca and Mg were in agreement with the certified values at the 95% confidence level (t-test; p < 0.05). The findings indicate that the liquid-liquid extraction method is reproducible, simple, and clean, and can be used as an alternative method of sample preparation for the determination of Na, K, Ca, and Mg in biodiesel samples.